Development of Direct Utilization Technology for CO2-Rich Natural Gas in South China Sea - Wu Qing (《中国工程科学》杂志社, 2021)
The natural gas in the South China Sea is characterized by a high CO2 content. The efficient development and precise utilization of CO2-rich natural gas resources in the South China Sea can help tackle climate change and achieve the goals of peaking carbon dioxide emissions and achieving carbon neutrality. In this article, we analyze the demand for and summarize the development status of the direct utilization of CO2-rich natural gas in the South China Sea. Subsequently, we focus on several key technologies and their application, including CO2-CH4 dry reforming, integration of CO2-rich natural gas to methanol, liquid fuel production through CO2 hydrogenation, and direct production of fine chemicals. We suggest that research on the CO2-rich natural gas resources in the South China Sea should be strengthened, an engineering platform for the comprehensive utilization of marine CO2-rich natural gas resources should be established, and the CO2-rich natural gas should be integrated with wind, solar, and nuclear energies to promote the sustainable development of the industry. Furthermore, the CO2-rich natural gas industry should be upgraded in the South China Sea, and a strategic alliance among production, education, research, and application should be established.